Comparison of the Effectiveness of Solution-Focused Brief Therapy and Compassion-Focused Therapy on Marital Adjustment of Married Women - Kheirkhah, Masoumeh; Bolghan-Abadi, Mustafa; Pourheydari, Sepideh (Psychology of Woman Journal, 2026)
Objective: This study aimed to compare the effectiveness of Compassion-Focused Therapy (CFT) and Solution-Focused Brief Therapy (SFBT) in improving marital adjustment among married women. Methods and Materials: This applied and experimental study used a pretest–posttest–two-month follow-up design with a control group. The statistical population included married women who attended the Hazrat Zainab Cultural Center in Mashhad, Iran, during 2022–2023. Sixty eligible participants were selected through convenience sampling and randomly assigned to three groups (CFT, SFBT, and control), but due to attrition, 16 participants remained in the CFT group, 18 in the SFBT group, and 18 in the control group. The Dyadic Adjustment Scale (DAS; Spanier, 1976) was used to measure marital adjustment. The CFT group attended twelve 90-minute weekly sessions based on Gilbert’s model, while the SFBT group participated in six 90-minute sessions following the Diamond approach. Data were collected at three time points (pretest, posttest, and two-month follow-up) and analyzed using repeated measures analysis of variance with SPSS-27. Findings: The results indicated significant main effects of time (p < .001, η² = .76) and group (p = .004, η² = .20) as well as a significant time × group interaction (p < .001, η² = .59) for marital adjustment. Post hoc Bonferroni tests showed that both the CFT and SFBT groups had significantly higher marital adjustment scores at posttest and follow-up compared with the control group (p < .001). However, no significant difference was found between the CFT and SFBT groups at either posttest or follow-up (p > .05). Conclusion: Both Compassion-Focused Therapy and Solution-Focused Brief Therapy effectively improved and sustained marital adjustment in married women, with comparable therapeutic impact.